Clustering of body composition, blood pressure and physical activity in Portuguese families. (March 2014) - de Chaves, Raquel Nichele; Baxter-Jones, Adam; Santos, Daniel; Gomes, Thayse Natacha; dos Santos, Fernanda Karina; de Souza, Michele Caroline; Diego, Vincent Paul; Maia, José
Abstract Aim: The purposes of this study were: (i) to identify familial resemblances in body fat, blood pressure (BP) and total physical activity (TPA); (ii) to estimate the magnitude of their genetic and environmental influences; and (iii) to investigate shared familial aggregation among these phenotypes. Subjects and methods: The sample comprised 260 nuclear families from Portugal. Body fat was assessed by bioelectrical impedance. BP was measured by an oscillometric device. TPA was estimated by the Baecke questionnaire. Familial correlation analyses were performed using Generalized Estimating Equations. Quantitative genetic modelling was used to estimate maximal heritability, genetic and environmental correlations. Results: Familial intra-trait correlations ranged from 0.15–0.38. Genetic and common environmental factors explained from 30%–44% of fat mass depots and BP and 24% of TPA. Genetic correlations were significant between BP and the fat mass traits (p < 0.05). Environmental correlations were statistically significant between diastolic BP and total body fat, trunk fat and arm fat (p < 0.05) and TPA and other phenotypes. Conclusions: The results suggest familial resemblance in the variation of body fat, BP and TPA, showing partial pleiotropic effects in the variation in body fat phenotypes and BP. TPA only shares common environmental influences with BP and body fat traits.